2008
DOI: 10.1007/s00534-007-1288-4
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic dissemination of hepatocellular carcinoma after local ablation therapy

Abstract: LAT for HCCs (even those less than 3 cm in diameter) adjacent less than 5 mm to the main or sectional portal vein possibly promotes intrahepatic dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…survival of optimal candidates may exceed 60-70% at 5 years, the main drawback being the high rate of disease recurrence during follow-up (>50% at 3 years). After surgical ablation, numerous cases are susceptible to metastasis (22). therefore, controlling the molecular factor of metastasis may be the suitable strategy after clinical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…survival of optimal candidates may exceed 60-70% at 5 years, the main drawback being the high rate of disease recurrence during follow-up (>50% at 3 years). After surgical ablation, numerous cases are susceptible to metastasis (22). therefore, controlling the molecular factor of metastasis may be the suitable strategy after clinical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators reported the risk factors of tumor seeding to be related to poor differentiation [14,17], the serum AFP level [17,20], subcapsular tumor location [17], preoperative biopsies [16], and the location of a tumor near the portal vein branches [20]. In our previous study, eight resected HCCs with intrahepatic dissemination were investigated after local ablation therapy, and five patients (62.5%) had an unsatisfactory safety margin, two (25%) had a prior needle biopsy, and four (50%) contained a poorly differentiated component in the tumor [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, several investigators have reported adverse effects and unusual patterns of recurrence after thermal ablation therapy [12][13][14][15][16][17][18][19][20]. Recently, some cases of treatment-related tumor seeding, especially needle tract tumor seeding [15][16][17] and intrahepatic dissemination have been reported [18][19][20]. Some investigators reported the risk factors of tumor seeding to be related to poor differentiation [14,17], the serum AFP level [17,20], subcapsular tumor location [17], preoperative biopsies [16], and the location of a tumor near the portal vein branches [20].…”
Section: Introductionmentioning
confidence: 99%
“…During the thermal ablation, the intratumoral pressure will increase which could promote tumor cells flow into the adjacent portal vein, and as a result, dissemination may occur throughout the liver. 8 Seki et al 9 also reported that some patients suffered from rapid tumor progression after RFA. Mulier et al 7 suggested RFA should achieve at least 1 cm ablative margin.…”
mentioning
confidence: 96%